Remittances, ICT and doing business in Sub-Saharan Africa - Simplice Asongu; Nicholas Biekpe; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2018)
Purpose - This study examines how linkages between information and communication technology (ICT) and remittances affect the doing of business. Design/methodology/approach - The focus is on a panel of 49 sub-Saharan African countries for the period 2000-2012. The empirical evidence is based on Generalised Method of Moments. Findings - While we establish some appealing results in terms of net negative effects on constraints to the doing of business (i.e. time to start a business and time to pay taxes), some positive net effects are also apparent (i.e. number of start-up procedures, time to build a warehouse and time to register a property). We also establish ICT penetration thresholds at which the unconditional effect of remittances can be changed from positive to negative, notably: (i) for the number of start-up procedures, an internet level of 9.00 penetration per 100 people is required while (ii) for the time to build a warehouse, a mobile phone penetration level of 32.33 penetration per 100 people is essential. Practical and theoretical implications are discussed. Originality/value - To the best of our knowledge, this is the first study to assess linkages between ICT, remittances and doing business in Sub-Saharan Africa.
Keywords: F24; F63; L96 O30; O55; 330; Remittances; ICT; Doing business; Development; Africa